Synthesis of carbon nanotubes and volatile organic compounds detection - Sobri, Shafreeza; Jasni, Jasronita; Md. Yasin, Faizah; Jamal, Siti Hasnawati; Janudin, Nurjahirah; Mohd Kasim, Noor Azilah (EDP Sciences, 2015)
In this work, the adsorption effect of volatile organic compounds (chloroacetophenone, acetonitrile and hexane) towards the change of resistance of CNTs pellet as sensor signal was investigated. CNTs used in this research were synthesized using Floating Catalyst – Chemical Vapor Deposition (FC-CVD) method in optimum condition. The synthesized CNTs were characterized using Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM) and Raman Spectroscopy. The variation of resistance changes towards the tested gases were recorded using a multimeter. CNTs sensor pellet showed good responses towards the tested gases, however, the sensitivity, response time and recovery time of sensor pellet need to be optimized.